Traditional Chinese medicines alleviate experimental chronic cerebral hypoperfusion injury through multi-components and multi-target mechanisms - Ma, Xiao-Ting; Lou, Bing-Yu; Liu, Jie; Liu, Bo (Frontiers in Pharmacology, 2025)
Traditional Chinese medicine (TCM) has been used in the treatment of vascular cognitive impairment and dementia caused by chronic cerebral hypoperfusion (CCH) in patients for hundreds of years. Ethnopharmacological researches have been conducted in recent years to elucidate their therapeutic effects on cognitive deficits and potential mechanisms in animal models. This manuscript critically reviewed recent 5-year experimental researches from PubMed on the topic, including 11 TCM formulae, 8 herb extracts, and 21 pure compounds extracted from TCM, including polyphenols, flavonoids, alkaloids, terpenoids, saponins, iridoid glycosides, glucosides, and others in rodent CCH models, using bilateral common carotid artery occlusion (BCCAO, 2VO), bilateral common carotid artery stenosis (BCAS), and unilateral common carotid artery occlusion (UCCAO). The underlying mechanisms are multiple, including the maintenance of blood brain barrier and endothelium integrity, the increase in cerebral blood flow, the amelioration of white matter lesions, the modulation of microglia M1/M2 phenotype, the scavenge of reactive oxidative oxygen species and reduction of proinflammatory factors, the maintenance of mitochondrial function, the inhibition of apoptosis, ferroptosis and pyroptosis, and the promotion of neuronal regeneration and angiogenesis through the regulation of gene/protein expressions, including the Toll, NF-κB, MAPK, PPARγ, and/or Nrf2 pathways. These mechanisms are not mutually exclusive, rather they play an integrated role to fortify the multi-components, multi-targets feature of TCM in the treatment of CCH and human vascular cognitive impairments.